Nano-calcium phosphate and dimethylaminohexadecyl methacrylate adhesive for dentin remineralization in a biofilm-challenged environment. Issue 10 (October 2020) - Tao, Siying; Su, Zhifei; Xiang, Zhenting; Xu, Hockin H.K.; Weir, Michael D.; Fan, Menglin; Yu, Zhaohan; Zhou, Xuedong; Liang, Kunneng; Li, Jiyao
Abstract: Objective: Dentin remineralization at the bonded interface would protect it from external risk factors, therefore, would enhance the longevity of restoration and combat secondary caries. Dental biofilm, as one of the critical biological factors in caries formation, should not be neglected in the assessment of caries preventive agents. In this work, the remineralization effectiveness of demineralized human dentin in a multi-species dental biofilm environment via an adhesive containing nanoparticles of amorphous calcium phosphate (NACP) and dimethylaminohexadecyl methacrylate (DMAHDM) was investigated. Methods: Dentin demineralization was promoted by subjecting samples to a three-species acidic biofilm containing Streptococcus mutans, Streptococcus sanguinis, Streptococcus gordonii for 24 h. Samples were divided into a control group, a DMAHDM adhesive group, an NACP group, and an NACP + DMAHDM adhesive group. A bonded model containing a control-bonded group, a DMAHDM-bonded group, an NACP-bonded group, and an NACP + DMAHDM-bonded group was also included in this study. All samples were subjected to a remineralization protocol consisting of 4-h exposure per 24-h period in brain heart infusion broth plus 1% sucrose (BHIS) followed by immersion in artificial saliva for the remaining period. The pH of BHIS after 4-h immersion was measured every other day. After 14 days, the biofilm was assessed for colony-forming unit (CFU) count, lactic acid production, live/dead staining, and calcium and phosphate content. The mineral changes in the demineralized dentin samples were analyzed by transverse microradiography. Results: The in vitro experiment results showed that the NACP + DMAHDM adhesive effectively achieved acid neutralization, decreased biofilm colony-forming unit (CFU) count, decreased biofilm lactic acid production, and increased biofilm calcium and phosphate content. The NACP + DMAHDM adhesive group had higher remineralization value than the NACP or DMAHDM alone adhesive group. Significance: The NACP + DMAHDM adhesive was effective in remineralizing dentin lesion in a biofilm model. It is promising to use NACP + DMAHDM adhesive to protect bonded interface, inhibit secondary caries, and prolong the longevity of restoration.